2001
DOI: 10.1046/j.1365-2958.2001.02654.x
|View full text |Cite
|
Sign up to set email alerts
|

IpaC from Shigella and SipC from Salmonella possess similar biochemical properties but are functionally distinct

Abstract: Invasion plasmid antigen C (IpaC) is secreted via the type III secretion system (TTSS) of Shigella flexneri and serves as an essential effector molecule for epithelial cell invasion. The only homologue of IpaC identified thus far is Salmonella invasion protein C (SipC/SspC), which is essential for enterocyte invasion by Salmonella typhimurium. To explore the biochemical and functional relatedness of IpaC and SipC, recombinant derivatives of both proteins were purified so that their in vitro biochemical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 32 publications
2
63
0
Order By: Relevance
“…Moreover, interspecies complementation performed with the Pseudomonas aeruginosa pcrV gene and a Y. pseudotuberculosis lcrV mutant (the proteins encoded by these two genes are homologous to one another) revealed that this component determines the size of the translocation channel (22). Additional studies in which such interspecies complementation experiments were performed revealed important information about the functions of different S. flexneri and S. enterica effectors (20,43).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interspecies complementation performed with the Pseudomonas aeruginosa pcrV gene and a Y. pseudotuberculosis lcrV mutant (the proteins encoded by these two genes are homologous to one another) revealed that this component determines the size of the translocation channel (22). Additional studies in which such interspecies complementation experiments were performed revealed important information about the functions of different S. flexneri and S. enterica effectors (20,43).…”
Section: Discussionmentioning
confidence: 99%
“…Shigella IpaB and IpaC each restored the ability of their corresponding Salmonella deletion strains to translocate effectors and invade nonphagocytic cells, but only expression of Shigella IpaC in Salmonella substantially altered the intracellular fate of this bacterium in epithelial cells and macrophages. This indicates that Shigella IpaC and Salmonella SipC confer different inherent vacuole lysis abilities to these two bacteria (6). Furthermore, enhanced phagosomal escape is not unique to Shigella IpaC, as complementation with the translocator protein CipC from another cytosolic pathogen, Chromobacterium, similarly enhanced vacuole lysis by Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…S. flexneri invasion of Henle 407 cells was monitored with a gentamicin protection assay as previously described (27,30). Henle 407 cells were seeded into 24-well plates and grown overnight to form preconfluent monolayers.…”
Section: Methodsmentioning
confidence: 99%